FUTURE TENSE IN THE PORTUGUESE LINGUISTIC TRADITION - P. E. Egizaryan (Вестник Кемеровского государственного университета, 2018)
The paper deals with the concept of the Future tense found in the Portuguese linguistic tradition. As the Portuguese linguistics appeared in the context of the European linguistic tradition, the first part of the article features the main views on the Future tense from the Antiquity to the Renaissance. The second part of the article is devoted to the Future tense in the Portuguese linguistics in XVI – early XX century, namely Latin and Portuguese grammar books, as well as those on other European and some non-European languages. The present research has shown that the Renaissance scholars already raised the questions that remain topical in the current linguistics. Those included the problems of relative tenses, the tense distance, the differences of the Future tense expression in languages with different structures, the tense as a complex functional semantic category that is not limited by the verb features, the close connection between the Future tense and the modality. Linguists of the subsequent epochs contributed to the investigation of these issues: the descriptions made in the early XX century are very close to the modern ones.